Analysable Chaos-based Design Paradigms For Cryptographic Applications - Abba, Abubakar (2024)
Chaos-based cryptography has garnered significant attention, with many designs focusing on obscuring security through complex designs that make them difficult to analyze, improper design structures (ad-hoc designs) with inaccurate keyspace justification. These compromise the standards of well designed, simple, and secure design principles in cryptographical design protocol and do not facilitate future cryptanalytic efforts. Moreover, to date, there have not been any chaos-based cryptosystems being implemented to secure real-world communications. This study proposes simple and analyzable paradigms based on well-established cryptographic principles (SPN and Feistel) to address these issues. First, an in-depth review is conducted on the current state-of-the-art in the field of chaos-based cryptographic algorithms to identify the challenges of various design and evaluation methods that have been developed over the years. A comprehensive analysis into a largely overlooked problem in chaos-based cryptosystems is conducted, highlighting their unusually large keyspaces. Multiple examples demonstrate instances of chaos-based ciphers overestimating keyspaces and reveal practical and theoretical challenges in key generation approaches. The study highlights recommendations and alternative solutions for utilizing secret keys in chaos-based cryptography. Then, a simple chaos-based key schedule that ensures the involvement of every bit of the secret key in the generation of round keys is proposed. The proposed key schedule successfully passed both the NIST and ENT statistical test suites, indicating that highly complex designs are unnecessary to achieve desirable security properties.